2015
DOI: 10.1002/chp.21262
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Participant Experience of an Online Train-the-Trainer Program for Bangladeshi Health Professionals: A Case Study Evaluation

Abstract: Online distance education can be effective in producing sustainable change in practitioner skills in developing countries. Future programs would benefit from a blended learning approach incorporating "face-to-face" instructor contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…In the context of sexual risk reduction counseling, “train-the-trainer” involves identifying a staff member who has some expertise in HIV/STI counseling and teaching that person how to train other staff in delivery of the counseling program. The “train the trainer” implementation strategy is considered a good choice for agencies with limited financial resources, such as CBOs and non-profit organizations [ 35 , 36 ]. Complete details of the intervention and the RCT are found elsewhere [ 28 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the context of sexual risk reduction counseling, “train-the-trainer” involves identifying a staff member who has some expertise in HIV/STI counseling and teaching that person how to train other staff in delivery of the counseling program. The “train the trainer” implementation strategy is considered a good choice for agencies with limited financial resources, such as CBOs and non-profit organizations [ 35 , 36 ]. Complete details of the intervention and the RCT are found elsewhere [ 28 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Though studies assessing the long-term outcomes of public health disaster preparedness educational interventions are uncommon, 2 other studies reported similar findings: 1 year after a training, attendees had retained their knowledge and/or confidence in the content provided. 12,13 The VISIBLE project focused on 4 tools available for free through the NLM: WISER, REMM, CHEMM, and TOXNET. These tools can be used for both pre-event planning and for responding to actual events.…”
Section: Discussionmentioning
confidence: 99%
“…14 An study on an online TTT program aimed at Bangladeshi health professionals reported that there was almost no dissemination of knowledge beyond the initial groups of individuals trained; the reason for the lack of follow-up was postulated to be a lack of confidence in the knowledge gained. 13 A statewide TTT program focused on public health preparedness in Maine involved 118 individuals in the initial training, and only 20% of those disseminated their training to others. 16 The findings from the VISIBLE program are in line with the better results reported in the New York TTT study in terms of the percentage of workshop attendees who disseminated the training to others and the approximate number of people educated in the second generation.…”
Section: Discussionmentioning
confidence: 99%
“…Efetividade da formação profissional ofertada na Educação a distância: validação teórica de um instrumento curso (BRESSEM et al, 2016), atitudes e crenças relacionadas à área do curso (BROWNLOW et al, 2015;CHO;SHIN, 2014), habilidades profissionais na área do curso (BROWNLOW et al, 2015;BLAZER et al, 2012;KENEFICK et al, 2014), desenvolvimento de competências profissionais (O'BRIEN; BROOM; ULLAH, 2015) e confiança para trabalhar na área do curso (BROWNLOW et al, 2015;O'BRIEN;BROOM;ULLAH, 2015).…”
Section: Atitudesunclassified